2018
DOI: 10.3390/nu10050608
|View full text |Cite
|
Sign up to set email alerts
|

Formula Milk Supplementation on the Postnatal Ward: A Cross-Sectional Analytical Study

Abstract: Breastfeeding rates are low in the UK, where approximately one quarter of infants receive a breastmilk substitute (BMS) in the first week of life. We investigated the reasons for early BMS use in two large maternity units in the UK, in order to understand the reasons for the high rate of early BMS use in this setting. Data were collected through infant feeding records, as well as maternal and midwife surveys in 2016. During 2016, 28% of infants received a BMS supplement prior to discharge from the hospital mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 80 publications
2
23
2
Order By: Relevance
“…The information on breastfeeding received by more than half (57.5%) of the respondents on their discharge from hospital was shown to be pertinent, and complied with BFHI recommendations. Our results turned out to be more favourable than those of the study by Biggs et al (2018), in which only 38% of the 102 respondents were adequately informed about breastfeeding. According to the evaluated answers of our study, less than one third of the respondents did not receive proper recommendations and advice from health providers about the frequency of breastfeeding, i.e., that the newborn should be breastfed on demand.…”
Section: Breastfeeding Education Provided To the Women By Health Provcontrasting
confidence: 74%
See 1 more Smart Citation
“…The information on breastfeeding received by more than half (57.5%) of the respondents on their discharge from hospital was shown to be pertinent, and complied with BFHI recommendations. Our results turned out to be more favourable than those of the study by Biggs et al (2018), in which only 38% of the 102 respondents were adequately informed about breastfeeding. According to the evaluated answers of our study, less than one third of the respondents did not receive proper recommendations and advice from health providers about the frequency of breastfeeding, i.e., that the newborn should be breastfed on demand.…”
Section: Breastfeeding Education Provided To the Women By Health Provcontrasting
confidence: 74%
“…In the Czech Republic, women are provided with information contrary to the BFHI protocols, such as the recommendation to use glucose to get infants to latch onto the breast more easily (Pokorná et al, 2016). In the UK, it is believed that the lack of time and heavy workload of midwives might contribute to their non-compliance with the BFHI protocols, despite the training they receive regarding formula feeding (Biggs et al, 2018). Use of a pacifier feeding bottle for formula supplementation, considered to be a negative phenomenon, was revealed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, 43.9% of formula supplementation was administered by HCPs, not parents, a higher rate than that reported recently in the UK. 18 We found that subjective reasons explained a very high proportion (75%) of total variance in our models with 'no latch' and 'mum unwell/exhausted' emerging as the strongest predictors for formula supplementation in contrast to objective factors such as low baby weight. This distinction is important since subjective factors can be modified more easily than objective factors.…”
Section: Discussionmentioning
confidence: 69%
“…Because AKGs increase Lactobacillus proliferation (94), they might also contribute to this indirect metabolic effect of breastfeeding. Today nearly 60% of infants are never breastfed (95,96) and childhood obesity may have its origins, at least in part, in insufficient breastfeeding (6)(7)(8)97). Components of the manufactured infant formula might also be responsible for the negative metabolic impact of the absence of breastfeeding (98).…”
Section: Discussionmentioning
confidence: 99%